2014
DOI: 10.1037/a0036994
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal transactions between personality and occupational roles: A large and heterogeneous study of job beginners, stayers, and changers.

Abstract: Social norms are central to theoretical accounts of longitudinal person-environment transactions. On the one hand, individuals are thought to select themselves into social roles that fit their personality. On the other hand, it is assumed that individuals' personality is transformed by the socializing pressure of norm demands. These 2 transactional directions were investigated in a large and heterogeneous 5-year longitudinal subsample of job beginners (n = 640, M age = 21.24), job stayers (n = 4,137, M age = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 64 publications
(76 reference statements)
5
76
2
Order By: Relevance
“…being architects), whereas individuals low in openness are more likely to choose and thrive in occupations that favour routines (e.g. being government tax and excise officials; for empirical evidence, see Denissen, Ulferts, Lüdtke, Gerstorf, & Muck, under review). To the degree that these niches have stable affordances and requirements, they will stabilize the traits that led people to seek out the respective niches in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…being architects), whereas individuals low in openness are more likely to choose and thrive in occupations that favour routines (e.g. being government tax and excise officials; for empirical evidence, see Denissen, Ulferts, Lüdtke, Gerstorf, & Muck, under review). To the degree that these niches have stable affordances and requirements, they will stabilize the traits that led people to seek out the respective niches in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…Zimmermann and Neyer () found corresponsiveness for openness in individuals who stayed abroad for longer periods (but not for short‐term stays and not for the other four traits). Finally, Denissen et al (in press) found corresponsive effects between personality and vocational change mainly for openness and extraversion but not for other Big Five traits.…”
Section: Individual Differences In Personality Changementioning
confidence: 97%
“…effects that lead people to experience these events in the first place) found that individuals who experienced specific life events had developmental trajectories that differed from those who did not experience these events (e.g. Denissen, Ulfers, Lüdtke, Muck, & Gerstorf, in press; Hutteman et al, 2014; Jackson, Thoemmes, Jonkmann, Lüdtke, & Trautwein, ; Lüdtke, Roberts, Trautwein, & Nagy, ; Reitz, Motti‐Stefanidi, & Asendorpf, ; Specht et al, ; Zimmermann & Neyer, ), supporting perspectives that emphasize the impact of life experiences as sources of individual differences in change. However, most of the revealed influences on personality development tended to be small when controlling for age (see also Allemand, Gomez, & Jackson, ; Costa, Herbst, McCrae, & Siegler, ), suggesting that changes in personality that can be traced back to experience of life events beyond general age trends are of limited impact.…”
Section: Individual Differences In Personality Changementioning
confidence: 99%
“…Of course, the corresponsive principle does not have to apply to all personality characteristics. For example, Zimmermann and Neyer () reported it for Openness but not for other FFM domains, whereas Denissen and colleagues () provided evidence for the corresponsive principle in Openness and Extraversion. Besides not being uniformly applicable to all FFM domains, it is possible that age differences in variance are masked in broad personality domains that aggregate numerous more specific personality characteristics.…”
Section: Age Differences In the Variance Of Personality Characteristicsmentioning
confidence: 99%